Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja dengan Stres Kerja sebagai Variabel Intervening pada PT Wasteforchange Alam Indonesia - Hendri Jopanda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
Human resources is one of the keys to the success of an organization, this is because human resources makes company work properly. Good employee performance will support the achievement of organizational goals and one of the triggers is the level of employee job satisfaction. Many factors can affect job satisfaction, some of them are leadership, work environment, and job stress. This research aims to find out and analyze the effect of leadership and work environment on job satisfaction with job stress as an intervening variable. The sample used in this research is all employees at PT Wasteforchange Alam Indonesia. The method used in this research is Path Analysis with SPSS 2.4 software as a tool for data processing. The results showed that leadership had a significant positive effect on employee job satisfaction, work environment has significant positive effect on employee job satisfaction, and job stress has significant negative effect on job satisfaction. Leadership has significant negative effect on work stress and work environment has significant negative effect on work stress. Leadership has a direct effect on employee job satisfaction without going through work stress, and work environment has a direct effect on employee job satisfaction without going through work stress.